Fiqh aqalliyah as a legal alternative to Halal standardization in Japan as a non-majority Muslim country - Zuhdi, Muhammad Luthfi; Shobichatul Aminah; Rasam, Zulifan (Indonesian Journal of Islam and Muslim Societies, 2024)
The increasing number of Muslim populations in the world has led to the development of the halal industry in both Muslim-majority countries and Muslim-minority countries. Japan is one of the non- Muslim majority countries that is actively developing the halal industry to meet the needs of Muslims both domestically and for export purposes. This research discusses the problems faced by Japan in meeting the needs of halal products for Muslims in Japan. Japan is experiencing problems related to halal standardization because the halal standards applied in Japan are halal standards from several Muslim-majority countries such as Indonesia, Malaysia and the United Arab Emirates. This study uses qualitative research methods through observation, in-depth interviews and FGD to explore the problems encountered in determining halal standards in Japan. This study found that the implementation of halal standards of Muslim majority countries to Muslim minority countries raises complex problems. For this reason, fiqh aqalliyah, which takes into consideration the geographical, social and cultural conditions of the community, can be a legal alternative for determining product halalness or halal standard in Muslim minority countries.